If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6-n=n-6
We move all terms to the left:
6-n-(n-6)=0
We add all the numbers together, and all the variables
-1n-(n-6)+6=0
We get rid of parentheses
-1n-n+6+6=0
We add all the numbers together, and all the variables
-2n+12=0
We move all terms containing n to the left, all other terms to the right
-2n=-12
n=-12/-2
n=+6
| (x-4)=135 | | a+3=9a-7 | | -6-4u=-3u | | 7x+5+28x=180 | | z^2+10z+30=0 | | 0.5x/5=1 | | (x+5)+3=4 | | 8-4w=-16 | | |x+5|+3=4 | | 4(y+7)=-y+3 | | (17x+8)=(12x-4) | | 3y-5=2y-4 | | 7-(2x+5)=3 | | 4(-3x+2)=-10(x-4)-14x | | 3(6-2.72)-4(2x-12)=0 | | −5x+7=−38 | | 3(6-2.72¨)-4(2x-12)=0 | | 5x-17=11x+5 | | 6c+13=19 | | -(x+4)=36 | | 2-2s=34s+132−2s=43 s+13 | | -10x+3/4x=200 | | x+81°=4x | | -2/3x=-26 | | 55=25-3p | | 3x+6x(x+3)=3(2x2+7x | | 1/1,000x=2.375 | | -2n-8=2n+4 | | 36p+18+8=35 | | 5(4-5x)=70 | | 3x+6x(x+3)=3(2x^2+7x) | | 1(p-1)=6(p-8)-12 |